TRANSICIONES EN LA COBERTURA Y USO DE LA TIERRA EN LA ZONA HÍDRICA CHAMBO – PENIPE: PERÍODO 1998-2007-2019 - Llumitaxi López, Luis Fernando (2020)
The objective of the research was to analyze the transitions in land cover and use in the Chambo-Penipe water zone: period 1998-2007-2019. Through multitemporal evaluation and quantification of changes and their comparison with random changes. The results were analyzed in terms of systematic transitions and intensities of change. The study consisted on 3 phases: the first is the treatment of satellite images and the application of the supervised classification model, generating three maps of land uses with eight categories: Water (Ag), Paramo (Pr), Forest (Bs), Crop (Cu), Wetland (Hu), Grassland (Pz), Infrastructure (Inf) and Snow (Nv). The maps were subjected to accuracy validation using the Kappa coefficient and obtaining almost perfect concordance forces. The second phase consisted of the analysis of systematic transitions in terms of profit and loss for each of the categories, where the results indicate that, throughout the study period, Hu is more susceptible to being replaced by other categories like Cu, Pr, Pz, and Nv. Finally, the intensity analysis at the speed level suggests that for the first nine years, the surface underwent a process of accelerated change, altering 43% of the landscape. At the nature level, the categories Hu, Inf, Cu, and Pz present active exchange statements. The significance level, in terms of gains, the Pz and Cu categories were evaluated, and in losses to Pr and Hu, identifying avoided and directed transitions.